The underlying regulatory mechanisms of colorectal carcinoma by combining Vitexin and Aspirin: based on systems biology, molecular docking, molecular dynamics simulation, and in vitro study - Chen, Dengsheng; Chen, Ying; Huang, Fang; Zhang, Xiaoling; Zhou, Yulv; Xu, Luning (Frontiers in Endocrinology, 2023)
Colorectal cancer (CRC) is a highly prevalent digestive system malignancy. Aspirin is currently one of the most promising chemopreventive agents for CRC, and the combination of aspirin and natural compounds helps to enhance the anticancer activity of aspirin. Natural flavonoids like vitexin have an anticancer activity focusing on colorectal carcinoma. Therefore, this study investigated the potential mechanism of action of the novel combination of vitexin and aspirin against colorectal cancer through network pharmacology, molecular docking, molecular dynamics simulation, and in vitro experiments. The results of network pharmacology suggested that vitexin and aspirin regulate multiple signaling pathways through various target proteins such as NFKB1, PTGS2 (COX-2), MAPK1, MAPK3, and TP53. Cellular experiments revealed that the combined effect of vitexin and aspirin significantly inhibited HT-29 cell growth. Vitexin dose-dependently inhibited COX-2 expression in cells and enhanced the down-regulation of COX-2 and NF-κB expression in colorectal cancer cells by aspirin. This study provides a pharmacodynamic material and theoretical basis for applying agents against colorectal cancer to delay the development of drug resistance and improve the prognosis of cancer patients.